Determination of iso-alpha-acids and reduced iso-alpha-acids (Rho, Tetra, Hexa) in hop products by HPLC using a modified version of Analytica-EBC Method 7.8: Submitted on behalf of the EBC Analysis Committee - Biendl, M.; Sørensen, S. B. (BrewingScience, 2004)
After the release of four international calibration standards for HPLC analysis of isomerised α-acids (DCHA-Iso, DCHA-Rho, Tetra and DCHA-Hexa), the EBC Analysis Committee decided to test a modification of Analytica-EBC Method 7.8 for the determination of iso-α-acids and reduced iso-α-acids in hop products. The method tested is essentially the method used by the International Subcommittee for Isomerised Hop α-Acids Standards to established the declared concentration of the international calibration standards and delivered together with the standards. The method is an isocratic HPLC method with detection at 270 nm, where the extinction coefficients for all forms of iso-α-acids and reduced iso-α-acids are quite similar in the mobile phase used. In the autumn 2001 a collaborative trial was carried out using four samples of hop products each containing one particular type of non-reduced or reduced iso-α-acids. Seven members of the EBC Analysis Committee, one member of AHA (Arbeitsgruppe Hopfenanalyse), three members of BCOJ and three American hop companies participated in the collaborative trial.